2020
DOI: 10.1177/1558944720964967
|View full text |Cite
|
Sign up to set email alerts
|

Does Undergoing Outpatient Hand Surgery Lead to Prolonged Opioid Use? A Comparison of Surgical and Nonsurgical Patients

Abstract: Background: Orthopedic surgical patients in general have been found to be at higher risk for developing opioid dependence in the postoperative period. However, there is conflicting evidence in the literature whether opioid exposure after hand surgery leads to prolonged use. In the absence of a nonoperative control group, it is not clear whether prolonged opioid use in hand surgical patients is related to undergoing a surgical intervention. The purpose of our study to compare opioid prescription fulfillment pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…20,21 Sacks et al 22 presented a psychological component of opioid consumption, showing that patients undergoing outpatient hand surgery with more catastrophizing pain and decreased mindfulness, attention, or awareness used more opioids after surgery. Wang et al 23 used the PDMP to compare the risks of prolonged opioid use in patients treated surgically versus those treated nonsurgically for common hand pathologies and found prior opioid use to be the only independent risk factor. Wong et al 24 described a preoperative opioid use rate of 23% in their patients who underwent upper extremity procedures.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Sacks et al 22 presented a psychological component of opioid consumption, showing that patients undergoing outpatient hand surgery with more catastrophizing pain and decreased mindfulness, attention, or awareness used more opioids after surgery. Wang et al 23 used the PDMP to compare the risks of prolonged opioid use in patients treated surgically versus those treated nonsurgically for common hand pathologies and found prior opioid use to be the only independent risk factor. Wong et al 24 described a preoperative opioid use rate of 23% in their patients who underwent upper extremity procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that preoperative exposure to controlled substances, including opioids, are predictive of prolonged postoperative opioid use [ 4 , 14 , 15 ]. We found that of the 108 patients who had received an additional opioid prescription postoperatively, 46 (42.6%) had received at least one opioid prescription within six months preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…After common hand and upper-extremity surgeries, inadvertent postoperative opioid prescribing can lead to dependency, abuse, diversion, death, and poor surgical and nonsurgical treatment outcomes; however, guidelines for appropriate opioid dosing and analgesic strategies are lacking. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Problem Statementmentioning
confidence: 99%
“…5 , 7 Greater initial prescriptions are associated with higher postoperative opioid usage in hand surgery. 23 , 24 , 25 Opioid use after most soft tissue hand surgeries is <5 opioid tablets, and even 0 when nonopioid analgesics are recommended. 5 , 7 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Opioid use after bony surgeries is higher than that for soft tissue surgeries.…”
Section: Current Evidence For Postoperative Opioid Requirementsmentioning
confidence: 99%
See 1 more Smart Citation